The Disaster Empire in The Wandering Earth 2 - Ping Zhu (Humanities)
This paper analyzes how the 2023 Chinese science fiction blockbuster The Wandering Earth 2 constructs what I call a “disaster empire”—a biopolitical system that seamlessly integrates authoritarian governance with capitalist logic through the constant threat of catastrophe. Through close readings of the film’s reappropriation of the Chinese Moving Mountain fable, its treatment of human sacrifice, and its portrayal of digital afterlife, I argue that the film presents a troubling vision where crisis enables the formation of a homogeneous time-space where the patriarchal family, the nation-state, and bio-capital converge to form a massive, enduring system of domination. While the film has been celebrated for its socialist values of collective survival, I demonstrate how it actually embodies the convergence of authoritarianism and global capitalism in its most insidious form. Drawing on theories of biopower, affect, and dead labor from Marxist scholars, this paper reveals how The Wandering Earth 2 functions as a work of prescriptive realism that faithfully encapsulates the deep drive of authoritarian capitalism.